The Impact of Political Polarization on Social Cohesion in a Multicultural Society - Wardani, Mufti (Sharia Journal and Education Center Publishing, 2025)
Political polarization is a growing phenomenon in multicultural societies, having a significant impact on social cohesion. This polarization can trigger social fragmentation, deepen the gap between groups, and hamper constructive dialogue in the public sphere. This research aims to analyze the impact of political polarization on social relations in multicultural societies, by highlighting factors that exacerbate divisions and identifying mitigation strategies that can be applied to strengthen social solidarity. Using a qualitative approach with literature review and in-depth interviews, this research reveals that political polarization is often exacerbated by ideological factors, religious differences, and the role of social media in reinforcing exclusive narratives. The results show that in societies with high levels of multiculturalism, the impact of political polarization is more complex and can lead to increased intolerance and social conflict. Therefore, inclusive policies and political education that emphasize the importance of dialogue and tolerance are needed to strengthen social cohesion amid political differences.